Improving Health Literacy of Elderly Posyandu Cadres: Hypertension Education in RW 04 Cipangeran Village - Ferdinan Sihombing; Linda Sari Barus; Widyadari Prasetyaningrum; Murtiningsih Murtiningsih; Zulkarnain Zulkarnain (Universitas 'Aisyiyah Bandung, 2025)
Hypertension is a prevalent health issue, particularly among the elderly population in rural areas. Community-based health efforts, such as those implemented through Elderly Integrated Health Posts (Pos Pelayanan Terpadu Lansia-Posbindu), rely heavily on the capacity and knowledge of health cadres. This community service program aimed to improve the knowledge and awareness of Posbindu cadres in RW 04, Cipangeran Village, Saguling District, regarding hypertension. The intervention was conducted through a planned and structured health education session, delivered by a professional community nursing educator. A total of nine cadres participated in this activity. Pretest and posttest assessments were carried out to measure changes in knowledge. The results showed an increase in posttest scores compared to pretest scores, with the average knowledge score rising from 62.22 to 81.11. Overall, this activity demonstrated that health education is a useful method to enhance the health literacy of community health cadres, potentially contributing to hypertension prevention and control efforts at the community level